Optimalisasi Branding, Pemasaran Digital, dan Hubungan Personal di RS Edelweiss Cianjur - Riyan Herdiansyah; Arlette Suzy Puspa Pertiwi; Yani Restiani Widjaja (CV. ALIM'SPUBLISHING, 2026)
This study aims to analyze the role of branding, digital marketing, and personal relationships in influencing new patients' decisions in choosing healthcare services at Edelweiss Cianjur Hospital. This research is motivated by the importance of marketing strategies in increasing the number of new patients amid increasingly competitive healthcare services. This study uses a qualitative approach with a descriptive method. Data were collected through in-depth interviews with new patients, medical staff, and a marketing manager selected through purposive sampling. Data analysis was conducted through transcription, coding, categorization, and thematic analysis. The results show that branding plays a role in building brand awareness and a positive image of the hospital, while digital marketing contributes to increasing patient awareness and interest through digital platforms such as websites and social media. In addition, personal relationships between medical staff and patients play an important role in building trust and patient satisfaction. The patient decision-making process consists of need recognition, information search, evaluation of alternatives, decision making, and post-service behavior. Patient satisfaction encourages loyalty and recommendations to potential new patients. This study concludes that hospital marketing strategies should be carried out in an integrated manner through strengthening branding, optimizing digital marketing, and improving the quality of personal relationships.